Radial Slits Maps of Unbounded Multiply Connected Regions - Yunus, AAM; Murid, AHM; Nasser, MMS (Amer Inst Physics, 2024)
This paper presents a boundary integral equation method for conformal mapping of an unbounded multiply connected region onto a radial slits region. Two linear boundary integral equations are constructed from a boundary relationship satisfied by an analytic function on an unbounded multiply connected region. These integral equations are uniquely solvable. The kernels involved in these integral equations are the adjoint generalized Neumann kernels. Two numerical examples are presented to show the effectiveness of the proposed method.